A Beautiful Thing: Mariachi and Femininity in Jalisco, Mexico - Mulholland, Mary-Lee (Anthropologica, 2013)
In Mexico, the western state of Jalisco is popularly represented as the birthplace of mariachi. An excessively cir culated national symbol, performances and performers of mariachi embody two important tenets of Mexican nationalism: machismo and mestizaje. In addition, Jalisco is also famous for its beautiful women, known for their light skin and piety. In this article I examine the increasing popular performance of women in all-female mariachis. Specifically, I am interested in how these mariacheras embody, mimic and contest their femininities in a highly gendered and racialized context in Jalisco.